2018
DOI: 10.3892/ol.2018.8180
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-192-5p suppresses the initiation and progression of osteosarcoma by targeting USP1

Abstract: Osteosarcoma is the most frequent primary malignant bone tumor. An increasing body of evidence has suggested that microRNAs (miRNA/miRs) have emerged as critical regulators in the initiation and progression of osteosarcoma. The present study explored the biological function of miR-192-5p and ubiquitin-specific protease 1 (USP1), and investigated whether miR-192-5p could directly interact with USP1 in osteosarcoma. The results revealed that miR-192-5p was significantly downregulated in osteosarcoma tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…In the present study, miR-192-5p was verified to be the upstream regulator of TRIP13 and was found to suppress cell motility in HCC cells. Consistent with our results, previous studies have reported low miR-192-5p levels in cancer, and that it suppresses the growth and metastasis of osteosarcoma, HCC, colon cancer and bladder cancer [14,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, miR-192-5p was verified to be the upstream regulator of TRIP13 and was found to suppress cell motility in HCC cells. Consistent with our results, previous studies have reported low miR-192-5p levels in cancer, and that it suppresses the growth and metastasis of osteosarcoma, HCC, colon cancer and bladder cancer [14,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 93%
“…The authors further demonstrated that miR-192-5p mediated cancer behaviours by targeting YY1. Zhou et al 31 also reported that miR-192-5p suppressed the initiation and progression of osteosarcoma by directly targeting USP1. In the present study, we observed that overexpression of miR-192-5p suppressed the proliferation, migration and invasion of lung cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Ectopic expression of miR-192 may be related to tumour occurrence as it exerts a significant effect on the progression of various malignancies. Recent studies have reported that miR-192 is considerably reduced in many malignant tumours and may be involved in regulating the proliferation, migration, and invasion of cancer cells in neoplasms 20,21,30,31 . For instance, Ji et al 30 suggested that miR-192-5p was significantly reduced in human bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the different effect of miR-192 has aroused our concern. It has been reported that miR-192 was downregulated in colon cancer, osteosarcoma, and bladder cancer [9][10][11]. However, upregulation of miR-192 was found in pancreatic ductal adenocarcinoma, neuroblastoma, and gastric cancer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%